Utility of Ocular Motility Tests in Orbital Floor Fractures with Muscle Entrapment That is Not Detected on Computed Tomography - Migliorini, Raffaele (Clin Ophthalmol, 2021)
PURPOSE: Determine the usefulness of ocular motility testing to detect the presence of muscle entrapment. MATERIALS AND METHODS: Cross-sectional study of patients with symptoms of diplopia secondary to facial trauma. Inclusion criteria: age between 20 and 80 years; symptoms of diplopia following facial trauma; presence of orbital floor fracture confirmed radiologically; presence of muscle entrapment confirmed at the time of surgery; best-corrected visual acuity of 0.6 or more. Exclusion criteria: muscle entrapment visible on computed tomography; candidate for immediate surgical correction; prior history of strabismus surgery. Outcome measures: Abnormal Head Position (AHP), Hirschberg Corneal Reflexes (CR), Cover/Uncover and Alternating Cover Test, Hertel exophthalmometry, Near Point of Convergence (NPC), Kestenbaum Limbus test, Red Filter test, and Hess screen test. RESULTS: Forty-six subjects (38 males, 8 females, mean age 27 ± 3.3 SD years). Pre-operative assessment: forty-six (100%) reported diplopia on the Red Filter test and showed some degree of abnormality on the Hess Screen test. Forty-two (91%) showed AHP. Forty-one (89%) had exophthalmometry values that differed 2 mm or more between the two eyes and insufficient NPC. Thirty-two (69.6%) showed deficits of 3 mm or more on the Kestenbaum Limbus test. Sixteen (35%) had abnormal Hirschberg corneal reflexes. Eleven (24%) demonstrated constant or intermittent strabismus. CONCLUSION: Ocular motility testing can differentiate non-invasively, pre-operatively, and cost-effectively the presence of muscle entrapment even when this is not visible on computed tomography.